Innovative Worker: Exploring the Mediation of Cognitive Dependency Factors between Leadership Support and Workplace Friendship - Ali, Ismail Haji; Fadhil, Muhammad; Basalamah, Jafar (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to examine the impact of leadership support and workplace friendship on employees' innovative behavior, as well as the mediating effect of cognitive dependency. This study utilizes 200 responses from employees at global ride-hailing firm, Grab. The partial-least-square structural-equation modelling (PLS-SEM) method is executed to analyze the hypotheses. The findings suggest the positive correlation between workplace friendship and innovative behavior, with cognitive dependency acts as a mediator between these two constructs. In particular, the role of cognitive reliance might be regarded as a significant determinant of employee behavior. This paper is a valuable resource for academics studying cognitive reliance, a topic that is often overlooked in past researches.